A Discourse Analysis of Rhetorical Devices and Linguistics Politeness in Political Speeches of the United States President Barack Obama - Đặng Thị Đông (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
People use language to express their feelings and to convey information. They can exchange the ideas and knowledge among each other. Using rhetoric devices, speakers would choose the strategies to have polite conversation. A variety of rhetorical devices and politeness strategies in his various speeches, which are factors attributing to Obama’s success in speech. He skillfully applied a variety of rhetorical devices in his various speeches. The thesis is to analyze rhetorical devices, linguistic politeness and their effects in some of his speeches to provide reference for the people who want to make a brilliant speech. And this is also the main reason why the thesis entitled “A Discourse Analysis of Rhetorical Devices and Linguistic Politeness in Political Speeches of the United States President Barack Obama.” to be conducted